Acoustic methods to suppress self-excited oscillations in spring-loaded valves. (February 2019) - El Bouzidi, Salim; Hassan, Marwan; Ziada, Samir
Abstract: Spring-loaded valves have been reported to experience self-excited vibration in reciprocating compressor installations as well as in safety relief devices of pressurized systems. Prior work by the authors has provided an experimental characterization (El Bouzidi et al., 2018a) and a theoretical model (El Bouzidi et al., 2018b) of the flow–sound-interaction mechanism which causes the self-excited vibration. It was found that the vibration occurred only when the fluid–structure interaction at the valve is coupled with acoustic reflections in the associated piping system. In other words, coupling with the pipe acoustics was essential for the initiation of the self-excited valve vibration. This investigation evaluates the effectiveness of three acoustic devices in suppressing the self-excited vibrations. The objective is to dampen the sound waves in the piping system and weaken its coupling with the valve oscillations. A concentric Helmholtz-type cavity resonator, an orifice plate, and an anechoic termination are placed at the downstream side of a model valve which exhibited strong self-excited vibration in previous investigations. The orifice plate was successful in eliminating the oscillation frequency, but its placement at the acoustic pressure node was critical. The concentric cavity resonator dampened the oscillations to very small amplitudes, but a knowledge of the oscillation frequency was necessary. Finally, the anechoic termination was also successful in suppressing the oscillation, but its practicality is rather limited in industrial pipelines. Highlights: Three acoustic passive filters were successfully devised to suppress valve vibrations. The anechoic termination showed that acoustic feedback is necessary for instability. The effectiveness of the orifice plate varied based on its placement location. The concentric cavity resonator required knowledge of the oscillation frequency to be effective.